2023
DOI: 10.14814/phy2.15655
|View full text |Cite
|
Sign up to set email alerts
|

Boric acid transport activity of marine teleost aquaporins expressed in Xenopus oocytes

Abstract: Marine teleosts ingest large amounts of seawater containing various ions, including 0.4 mM boric acid, which can accumulate at toxic levels in the body. However, the molecular mechanisms by which marine teleosts absorb and excrete boric acid are not well understood. Aquaporins (Aqps) are homologous to the nodulin‐like intrinsic protein (NIP) family of plant boric acid channels. To investigate the potential roles of Aqps on boric acid transport across the plasma membrane in marine teleosts, we analyzed the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Furthermore, we previously reported that Japanese pufferfish (Takifugu rubripes) Aqp9a transports water, urea, and boric acid, but little glycerol (11), and that the set of amino acids in ar/R was consistent with the tetrapod Aqp10 mutants examined in this study. Additionally, human…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Furthermore, we previously reported that Japanese pufferfish (Takifugu rubripes) Aqp9a transports water, urea, and boric acid, but little glycerol (11), and that the set of amino acids in ar/R was consistent with the tetrapod Aqp10 mutants examined in this study. Additionally, human…”
Section: Discussionsupporting
confidence: 82%
“…Xenopus laevis oocytes were dissociated with collagenase, as previously described (11,12,23), and injected with 50 nL of water or a solution containing 0.5 ng/nL cRNA (25 ng/oocyte) using the Nanoject-II injector (Drummond Scientific, Broomall, PA, USA). Oocytes were incubated in the OR3 medium at 16 °C and observed for 5 d after injection.…”
Section: Expression Of Aqp10s In Xenopus Oocytesmentioning
confidence: 99%
See 2 more Smart Citations